How to Prescribe Topical Steroids - Matthew Perez (Association of American Medical Colleges, 2014)
Abstract Introduction Although topical steroids are frequently prescribed in primary care, practical formal instruction is rare to nonexistent and misuse of topical steroids is widespread. To address this, this streamlined talk was created as something that could be presented during a break in clinic or lunch. The intended audience includes primary care providers of all levels, residents, and clinical graduate students (ARNP, PA). Methods This 20-30 minute presentation reviews how to safely and effectively prescribe topical steroid medications and instruct patients in their proper use. Topics covered include diagnoses that respond to steroids as well as the treatment duration, quantity, strength, and vehicle selection (ointment, cream, solution) of various steroids. The session concludes with patient cases to practice prescribing topical steroids. This can be presented one-on-one or in large groups. A one-page summary of practical use tips is also given to learners for future reference. Results Medical students, ARNP students, family medicine residents, and practicing clinicians have reported that this talk was practical and useful over the past three years. Discussion This presentation follows the guidelines by Reynolds to limit text and teach primarily with pictures and the presenter's words.